The prevalence of symptoms of depression and anxiety, and the level of life stress and worry in New Zealand Māori and non-Māori women in late pregnancy. (February 2017) - Signal, T Leigh; Paine, Sarah-Jane; Sweeney, Bronwyn; Muller, Diane; Priston, Monique; Lee, Kathryn; Gander, Philippa; Huthwaite, Mark
Objective: To describe the prevalence of symptoms of depression and anxiety, and the level of life stress and worry in late pregnancy for Māori and non-Māori women. Methods: In late pregnancy, women completed a questionnaire recording their prior history of mood disorders; self-reported current depressive symptoms (⩾13 on the Edinburgh Postnatal Depression Scale), current anxiety symptoms (⩾6 on the anxiety items from the Edinburgh Postnatal Depression Scale), significant life stress (⩾2 items on life stress scale) and dysfunctional worry (>12 on the Brief Measure of Worry Scale). Results: Data were obtained from 406 Māori women (mean age = 27.6 years, standard deviation=6.3 years) and 738 non-Māori women (mean age = 31.6 years, standard deviation=5.3 years). Depressive symptoms (22% vs 15%), anxiety symptoms (25% vs 20%), significant life stress (55% vs 30%) and a period of poor mood during the current pregnancy (18% vs 14%) were more prevalent for Māori than non-Maori women. Less than 50% of women who had experienced ⩾2 weeks of poor mood during the current pregnancy had sought help. Being young was an independent risk factor for depressive symptoms, significant life stress and dysfunctional worry. A prior history of depression was also consistently associated with a greater risk of negative affect in pregnancy. Conclusion: Antenatal mental health requires at least as much attention and resourcing as mental health in the postpartum period. Services need to specifically target Māori women, young women and women with a prior history of depression.